Eine Bezeichnung für libysche Warlords? - Römer, Malte (Zeitschrift für ägyptische Sprache und Altertumskunde, 2012)
The title aA n xrw , borne by Libyans, is mainly known from hieroglyphic inscriptions. In this article, additional evidence from papyri of the ThirdIntermediate Period is presented, which has been unnoticed or misunderstood until now. The meaning of this title is problematic. The previously suggested translation as “Great one of the enemies” does not explain its adoption by those enemies in question, namely the Libyans, for their own nobles. Therefore a different meaning is suggested.